ANOMALOUS ELECTRICAL CONDUCTIVITY OF THE CRUST OF EASTEN PART OF PREASOV MEGABLOCK - Burahovich, T.; Kushnіr, A.; Zaitsev, G.; Shyrkov, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article deals the spatial parameters of high electric conductivity anomalies in the depths of the earth's crust, and their nature, especially on the boundaries of the metallogenic and seismic generating structures.